2020
DOI: 10.1101/2020.01.15.908400
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distinguishing the neural correlates of perceptual awareness and post-perceptual processing

Abstract: To identify the neural correlates of perceptual awareness, researchers often compare the differences in neural activation between conditions in which an observer is or is not aware of a target stimulus. While intuitive, this approach often contains a critical limitation: In order to link brain activity with perceptual awareness, observers traditionally report the contents of their perceptual experience. However, relying on observers' reports is problematic because it makes it difficult to know if the neural re… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…This discussion is clearly beyond the scope of the present report, but the strong relation we discovered between the presence of a GE and the ability to report subjectively global deviance advocates for this second hypothesis (19). Moreover, scalp topography of the ERP GE corresponds to a P3b component (17), and a current scientific debate questions the meaning of P3b: is it a direct neural signature of conscious access, or rather a post-perceptual correlate of cognitive events that are posterior in time to conscious access (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)? Interestingly, the single consensual point of this debate consists of considering that P3b presence does require conscious processing (even if it is not the neural signature of conscious access).…”
Section: Discussionmentioning
confidence: 62%
“…This discussion is clearly beyond the scope of the present report, but the strong relation we discovered between the presence of a GE and the ability to report subjectively global deviance advocates for this second hypothesis (19). Moreover, scalp topography of the ERP GE corresponds to a P3b component (17), and a current scientific debate questions the meaning of P3b: is it a direct neural signature of conscious access, or rather a post-perceptual correlate of cognitive events that are posterior in time to conscious access (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)? Interestingly, the single consensual point of this debate consists of considering that P3b presence does require conscious processing (even if it is not the neural signature of conscious access).…”
Section: Discussionmentioning
confidence: 62%
“…With that said, we note that P3b amplitude was also associated with variability in performance, though to a somewhat lesser degree. It is therefore possible that control allocation was already being determined at this early stage of the trial but, in conjunction with past findings 67 , it is equally or perhaps more likely that the P3b indexed the initial evaluation of the motivational relevance of cued incentives, as we originally hypothesized. Consistent with our original interpretation, we found that the amplitude of the P3b (but not CNV) decreased over the course of the session, potentially reflecting decreased attentiveness to the cues.…”
Section: Discussionmentioning
confidence: 80%
“…Using a novel inattentional blindness paradigm, they showed that the P3, which was initially thought to discriminate information that did or did not enter the global workspace (see Dehaene, 2014, p.180), was driven by task relevance and not conscious access. This result was recently replicated in a standard masking paradigm (Cohen, et al, 2020) showing unequivocally that the P3 is related to task relevance and is not a necessary signature of conscious access.…”
Section: Introductionmentioning
confidence: 73%